2010
DOI: 10.1109/tns.2010.2047405
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Fractional Order Phase Shaper for Iso-Damped Control of a PHWR Under Step-Back Condition

Abstract: Phase shaping using fractional order (FO) phase shapers has been proposed by many contemporary researchers as a means of producing systems with iso-damped closed loop response due to a stepped variation in input. Such systems, with the closed loop damping remaining invariant to gain changes can be used to produce dead-beat step response with only rise time varying with gain. This technique is used to achieve an active step-back in a Pressurized Heavy Water Reactor (PHWR) where it is desired to change the react… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 24 publications
2
60
0
Order By: Relevance
“…Recently, Saha et al [8] proposed an active rod drop with a robust controller comprising of a FO phase shaper and a Linear Quadratic Regulator (LQR) based PID for an active motor driven step-back. The approach, presented in this paper is an improvement over the active step-back in [8] and in this case the actuator can be driven by a single robust PI λ D μ controller.…”
Section: Fractional Order Modeling Of a Phwr Undermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Saha et al [8] proposed an active rod drop with a robust controller comprising of a FO phase shaper and a Linear Quadratic Regulator (LQR) based PID for an active motor driven step-back. The approach, presented in this paper is an improvement over the active step-back in [8] and in this case the actuator can be driven by a single robust PI λ D μ controller.…”
Section: Fractional Order Modeling Of a Phwr Undermentioning
confidence: 99%
“…As a result, the linearized models of a reactor gets changed depending on the operating conditions i.e. the initial power level at which a step-back is initiated in addition to the level of control rod drop [8], [9]- [10]. Thus, at different levels, step-back would require a different controller.…”
Section: Introductionmentioning
confidence: 99%
“…Saha et al [37][38][39] devised a fractional order PID controller of the identification model and reduced order model for a CANDU type pressurized heavy water reactor with practical test data in order to regulate this reactor power. The combination of the fractional order PID control and the new neural network algorithm to optimize controller parameters was effectively exploited by Zhao et al [40] to develop a PWR core power control system.…”
Section: Fractional Order Controlmentioning
confidence: 99%
“…Improving power regulation technology of cores by the introduction of control algorithms is an important measure for safety and availability of NPPs. Over the decades, many control algorithms have been exploited and applied by researchers to core power regulations, which are the stateor output-feedback control with a state observer [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], the optimal control [18,19], the neural network or fuzzy intelligent control [20][21][22][23][24][25], the model predictive control [26][27][28], the H ∞ robust control [29][30][31], the sliding model control [32][33][34][35], the fractional order control [36][37][38][39][40][41] and other control algorithms [42][43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%
“…This led to wide spread research interest in FO control (Podlubny 1999;Monje et al 2010;Das 2010;Caponetto et al 2010;Baleanu et al 2012;Bandyopadhyay and Kamal 2014) and FO signal processing (Magin et al 2011). The arbitrariness in the order of FO systems offers additional tuning parameters in the FO controller making it a potential candidate for controlling complex systems like diffusion (Ozdemir and Iskender 2010); pressurized heavy water reactor (Saha et al 2010); wind energy (Melicio et al 2010); twin rotor MIMO system (Mishra and Purwar 2014); mechatronics, biological systems, and many more (Monje et al 2010). Besides, a number of FO electronic systems, like FO oscillators (Radwan et al 2008), FO filters Tripathy et al 2013Tripathy et al , 2015Tseng 2007;Soltan et al 2015;, FO PLL (Tripathy et al 2015), and many others (Biswas et al 2006;Mondal and Biswas 2011; have been developed and have shown promising results.…”
Section: Introductionmentioning
confidence: 99%